Outcome quality of small- to medium- sized enterprise–based alliances - Weaver, K.Mark; Dickson, Pat H. (Journal of Business Venturing, 1998)
Proponents of transaction cost theory have assumed that alliance formation is motivated by environmental uncertainty, with the structure and outcomes of alliance relationships being determined by the costs versus benefits of opportunism on the part of alliance participants (Williamson 1985; Zaheer and Venkatraman 1995). Williamson argued that cooperative relationships driven by perceived efficiency are inherently prone to opportunism or “self-interest seeking with guile” (1975, p. 6). In alliance relationships, opportunism generally takes the form of negative departures from the behavioral norms established for the alliance and is usually motivated by the firm leader’s desire to improve the firm’s position, regardless of the cost to the alliance (Parkhe 1993a). The traditional focus of transaction cost theory has been on the norms established by the formal alliance relationship. These contractual mandates encompass both goal-based and relationship-based expectations. Failure to meet these types of expectations significantly, but not completely, explains the quality of outcomes for alliance relationships. A growing body of research on social control theory suggests that the social embeddedness of the alliance relationship may also establish behavioral norms against which opportunistic departures may be judged Ouchi 1979, Parkhe 1993b. Such norms are extracontractual or taken-for-granted expectations established by both the prior experience of the firms’ leaders and the placement of the firms’ alliance relationships within the network of interpersonal relationships maintained by the firms’ leaders. This study explores the relative impact of negative departures from both contractual and extracontractual behavioral norms on the quality of alliance outcomes, while controlling for a wide range of environmental and firm-specific factors suggested to have an impact on alliance outcome quality. Norwegian manufacturing firms that met the study’s size criteria and belonged to any one of 10 industry types were surveyed. From a list of over 7,000 small- to medium-sized enterprises (SMEs), we randomly selected and mailed surveys to the key decision leaders of over 2,500 firms, ultimately identifying, of the 433 (17.6%) owners and general managers responding, 252 (58%) that maintained alliance relationships. The results of this study challenge several assumptions regarding the determinants of alliance outcomes. A number of resource- and environment-based factors, including the firm’s industry, size, and financial strength, are not found to significantly influence alliance outcomes. The financial return provided by the SME’s alliance relationships, as an indicator of goal-based determinants, was found to be the most important factor related to outcome quality, but the results also suggested that contract noncompliance and the perceived behaviors of the SME’s alliance partners are significant as well. Additionally, the notion that SME-based alliance relationships are generally marked by assumptions of trust rather than opportunism was supported. When partner behaviors are seen or perceived to be inconsistent with either contractually mandated or socially obligated expectations, the outcomes of those relationships are negatively effected, even when the financial goals have been met. An additional finding of this study was that firm leaders make judgments regarding the quality of alliance outcomes in light of their cumulative experience with alliance relationships.